Fabric Woven Textile Antenna for Medical Applications. Issue 1 (June 2021) - Sugunavathy, S; Sudha, V K; Parthiban, D.
Abstract: Wearable Technologies are key driving forces in transforming conventional Health care systems to an unprecedented prototype of Connected Health (CH) Care systems. In these Connected Health Care systems, the role of wearable antennas cannot be overlooked. For designing reliable wearable systems, antenna should be of low profile, compact in size, lighter in weight, conformal and flexible to fasten it on Patient's attire. As a contribute approach, this paper aims at proposal of microstrip patch antenna that resonates at ISM band of 2.4GHz. The proposed antenna is built on Rubber substrate with Polyester (Ground plane) as a conducting fabric driven by a microstrip line feeding structure. Improvement in antenna performance could be achieved by using Defected Ground Structure (DGS) polyester ground. Performance characteristics such as Directivity, Gain, VSWR and Radiation Pattern are measured. Specific Absorption Rate (SAR) value for Human Phantom model was calculated by on Body Simulation. The antennas and the human body tissue effects is observed in CST tool.